Muhammadiyah dan Pelayanan Sosial Di Bidang Kesehatan dan Sosial Kemasyarakatan - Jemi Anggara; Rahmat Rudiyanto (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The aim of this research is to describe the social and health movements carried out by Muhammadiyah as one of the leading Islamic organizations in Indonesia. This research uses a qualitative methodology with a library approach. The research results show that Muhammadiyah's contribution to the field of social and health services is very large with the birth of various Muhammadiyah Charity Businesses such as hospitals, maternity homes, polyclinics, orphanages, nursing homes, and lazismu.